Exploring Value-Based Leadership in Fostering a Religious School Culture Through Character-Oriented Educational Practices - Khoirun Nisak; Abdul Hamid; Hemas Haryas Harja Susetya (Journal of Educational Management Research, 2026)
This study aimed to analyze the implementation of value-based leadership in fostering a religious school culture, identify the factors that support and hinder its implementation, and examine its implications for developing students' religious character. A qualitative case study approach was employed to obtain an in-depth understanding of leadership practices within an Islamic junior secondary school. Participants included the principal, vice principal, teachers, administrative staff, and students, who were selected through purposive sampling. Data were collected using semi-structured interviews, observations, and document analysis, and were analyzed following the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings revealed that value-based leadership was implemented through exemplary leadership, the habituation of religious practices, the reinforcement of Islamic values, and the integration of religious programs into daily school activities. Its implementation was supported by a conducive Islamic boarding school environment, institutional commitment, and structured religious programs, while differences in students' motivation and limited instructional time emerged as the primary challenges. The study implies that value-based leadership serves as an effective strategy for cultivating a sustainable religious school culture by strengthening character formation, promoting moral responsibility, and fostering the internalization of religious values within educational institutions.